Development of a practical engineering project and heat transfer solver to support a thermal-fluid system design course at NTU. (4th March 2008) - Tan, F.L.; Fok, S.C.
This paper describes the utilisation of industry design projects to engage students in the practical utilisation of thermal-fluid knowledge. The proposed framework in a new thermal system design course is discussed based on the development of cooling systems for electronic devices such as computers and personal digital assistants. By incorporating practical design into the thermal-fluid courses, it is hoped that the curriculum would enhance the skills of the graduates and equip them with practical knowledge to function with competencies and creativities in the engineering profession.